Silence is golden? Relationship between silent behavior among online community members and operation performance from the perspective of personality trait - Pei, Xueliang; Lyu, Fanying; Xiong, Xiaojun; Wei, Anpin; Guo, Jianing; Zhou, Wenxin (Frontiers in Psychology, 2022)
As companies are transforming their branding, marketing, operations, and research and development (R&D) by running online communities to build their core competitive advantages in the digital era, the silent majority is still the norm in the online community and has become the focus of online community operations. Thus, it has become the core issue that why silent behavior of online community members occurs and its impact on operation performance of the online community. According to the traditional theory of organizational behavior, this study focuses on the theoretical model of the relationship between proactive personality, silent behavior of online community members (acquiescent, defensive, and prosocial silence), and operation performance of the online community, and further analyzes the impact of community identification on these relationships. Eight hundred online community members in China participated in this study. The results indicate that: (1) proactive personality has a significant negative impact on acquiescent silent and defensive silent behavior of the online community members, and a significant positive impact on prosocial silent behavior of the online community members; (2) The acquiescent silence and defensive silence have a significant negative impact on online community operation performance, whereas prosocial silence has a significant positive impact on community operation performance; (3) The acquiescent silence and defensive silence have a significant mediating effect on the relationship between proactive personality and community operation performance; (4) Online community identification has a moderating effect on the relationship between silent behavior and online community operation performance. The study proposes the mechanisms and double-edged sword effects of the silent behavior of online community members from the perspective of personality traits. On the one hand, it generalizes the research of traditional organizational silent behavior theory to the context of the online community. On the other hand, it provides reference and inspiration for the theoretical research and practical management of silent behavior of online community members.